Risk factors for preterm labor. - Rodrigues, T (1998)
Most studies investigating preterm risk factors include medically induced preterm labor due to fetal or maternal complications and do not distinguish preterm labor from preterm premature rupture of membranes. Thus, the objective of this study was to determine the proportion of the three types of preterm birth and identify risk factors for spontaneous preterm labor in a sample of pregnant women who delivered at two level III units.From January to October 1996, we interviewed 385 women with live preterm newborns and, as controls, 357 mothers of term newborns. Preterm births were classified as preterm labor, preterm premature rupture of membranes and iathrogenic preterm. Independent associations between maternal sociodemographic, constitutional, nutritional and obstetric characteristics and preterm labor were identified using logistic regression analysis.In this sample of preterm births, 29% corresponded to preterm labor, 49% to preterm premature rupture of the membranes and 22% were iathrogenic preterm. The identified risk factors for preterm labor were multiple gestation, no paid work during pregnancy, less than six prenatal care visits, arm circumference less than 26 cm and previous preterm or low birth-weight. Gestational bleeding during the first or third trimester was significantly associated with preterm labor.As previously recognized, multiple gestation, prior preterm or low birthweight and gestational bleeding are established risk factors for preterm labor. However, prenatal care, maternal work and nutritional status have also been revealed as important issues in preterm risk, deserving special interest since they are susceptible to preventive intervention.